The Role of School Supervisors in Differential Mentoring to Increase the Leadership Capacity of School Principals - Margiyanto Margiyanto; Taufiq Harris; Furqon Wahyudi (Al Hikmah: Journal of Education, 2026)
This study examines the role of school supervisors in implementing differentiated mentoring to enhance principals’ leadership capacity. Variations in leadership capacity among principals are influenced by contextual, organizational, and individual factors, while supervisory practices often remain uniform. This study aims to develop an effective differentiated mentoring model tailored to principals’ needs. A qualitative multi-site case study was conducted at SMA Negeri 1 Sidayu and SMA Muhammadiyah 10 GKB in Gresik Regency. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that effective differentiated mentoring begins with diagnostic mapping of principals’ leadership capacity, followed by the selection of appropriate mentoring strategies such as facilitation, mentoring, and coaching. The results show that principals with high capacity benefit from facilitative and coaching approaches, while those with moderate capacity require mentoring combined with coaching. The integration of reflection and growth mindset strengthens leadership development, and religious approaches are relevant in faith-based schools. This study contributes to educational management by proposing a contextual and adaptive differentiated mentoring model for improving principals’ leadership capacity.